2011
DOI: 10.1136/bmjqs.2009.039339
|View full text |Cite
|
Sign up to set email alerts
|

Resident-initiated interventions to improve inpatient heart-failure management

Abstract: Background Third year internal medicine residents participating in a quality improvement rotation identified gaps between the Joint Commission’s ORYX quality guidelines and clinical practices for the inpatient management of heart failure (HF) at the William S. Middleton Memorial Veterans Hospital. Residents focused on the performance metrics associated with tobacco cessation counseling documentation, ejection fraction assessment, and angiotensin converting enzyme inhibitor (ACEI)/angiotensin receptor blocker (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“… 53 Only one of three studies 34 57 58 evaluating multifaceted interventions that included audit and feedback as well as reminders reported significant increases in LVEF assessment. 34 Education, 32 reminders 27 and changes in medical records systems 38 did not significantly increase LVEF assessment…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“… 53 Only one of three studies 34 57 58 evaluating multifaceted interventions that included audit and feedback as well as reminders reported significant increases in LVEF assessment. 34 Education, 32 reminders 27 and changes in medical records systems 38 did not significantly increase LVEF assessment…”
Section: Resultsmentioning
confidence: 91%
“… 46 In contrast, interventions that did not produce significant improvements included audit and feedback 23 and changes to medical records systems. 38 One study, on financial incentives, did not report statistical significance.…”
Section: Resultsmentioning
confidence: 99%
“…[49][50][51][52] The least common intervention used individual projects in which the trainee worked independently. Most of these studies were rated 'good,' [53][54][55][56] and one received a 'fair'. 57 Most of these studies showed no significant clinical outcomes, 53 55-57 while one study showed significant improvement in care for heart failure patients.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…57 Most of these studies showed no significant clinical outcomes, 53 55-57 while one study showed significant improvement in care for heart failure patients. 54…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Most of these studies were rated ‘good,’53–56 and one received a ‘fair’ 57. Most of these studies showed no significant clinical outcomes,53 55–57 while one study showed significant improvement in care for heart failure patients 54…”
Section: Resultsmentioning
confidence: 99%